Alone in the dark II - Boll, Uwe; Scheerer, Peter; Roesch, Michael ([S.l] : The Myth Entertainment, 2008)
Mine workers find the remnants of an ancient vanished civilization named Abkani that believed there are the worlds of light and darkness. When they opened the gate between these worlds ten thaousand yeras ago, something evil slipped through before the gate was closed
Title from title screen
Executive producer, Kenneth Del Vecchio, Matthias Triebel, Hans Baer
Cast: Rick Yune, Rachel Specter, Bill Moseley, Tara Reid, Crispin Glover, Darren Shahlavi, Stephen Dorff
DVD Format
Audio system English 5.1 and English 2.0
With English, Chinese and Malay subtitles
Keywords: Private investigators -- Drama; Supernatural -- Drama; Horror films